Polifonie : storia e teoria della coralità (2001)
"Polifonie" is devoted to the study of monophonic and polyphonic vocal music from the Middle Ages to the present day, within the Western art tradition and beyond. Its scope includes source-studies, palaeography, textual criticism, performance practice, music theory, music analysis, historical and archival studies, and interdisciplinary research in fields such as literature and art. The journal aims at b the most recent research in these fields with the goal of offering a critical forum for fruitful exchanges among scholars, composers, choral conductors and singers. (Verlag)